Auditory temporal resolution and backward masking in musicians with absolute pitch - Leite Filho, Carlos Alberto; Rocha-Muniz, Caroline Nunes; Pereira, Liliane Desgualdo; Schochat, Eliane (Frontiers in Neuroscience, 2023)
Among the many questions regarding the ability to effortlessly name musical notes without a reference, also known as absolute pitch, the neural processes by which this phenomenon operates are still a matter of debate. Although a perceptual subprocess is currently accepted by the literature, the participation of some aspects of auditory processing still needs to be determined. We conducted two experiments to investigate the relationship between absolute pitch and two aspects of auditory temporal processing, namely temporal resolution and backward masking. In the first experiment, musicians were organized into two groups according to the presence of absolute pitch, as determined by a pitch identification test, and compared regarding their performance in the Gaps-in-Noise test, a gap detection task for assessing temporal resolution. Despite the lack of statistically significant difference between the groups, the Gaps-in-Noise test measures were significant predictors of the measures for pitch naming precision, even after controlling for possible confounding variables. In the second experiment, another two groups of musicians with and without absolute pitch were submitted to the backward masking test, with no difference between the groups and no correlation between backward masking and absolute pitch measures. The results from both experiments suggest that only part of temporal processing is involved in absolute pitch, indicating that not all aspects of auditory perception are related to the perceptual subprocess. Possible explanations for these findings include the notable overlap of brain areas involved in both temporal resolution and absolute pitch, which is not present in the case of backward masking, and the relevance of temporal resolution to analyze the temporal fine structure of sound in pitch perception.